Fuzzy TOPSIS method for ranking barriers to environmentally conscious manufacturing implementation: government, industry and expert perspectives. (1st January 2014) - Mittal, Varinder Kumar; Sangwan, Kuldip Singh
A growing number of organisations have begun working towards implementation of Environmentally Conscious Manufacturing (ECM) because of increased concerns about the pollution increase, natural resources depletion and global warming. But some barriers hinder the implementation of ECM systems. In order to mitigate these barriers, the ranking of barriers is very essential as high-ranked barriers can be taken up first to address the issue more effectively within the availability of resources and capacity to improve environment. This paper aims at identifying and ranking barriers to ECM implementation. Twelve barriers have been identified and grouped as economic, internal, policy and societal barriers. A fuzzy TOPSIS multi-criteria decision model has been developed to rank these barriers from government, industry and expert perspectives by using the data inputs from various sources in India. The ranking of the barriers from different perspectives will help the decision/policy makers in government and industry to mitigate these barriers in an effective manner.